Fine root dynamics for forests on contrasting soils in the Colombian Amazon (2009)
It has been hypothesized that as soil fertility increases, the amount of carbon allocated to below-ground production (fine roots) should decrease. To evaluate this hypothesis, we measured the standing crop fine root mass and the production of fine roots (2 mm) by two methods: (1) ingrowth cores and, (2) sequential soil coring, during 2.2 years in two lowland forests growing on different soils types in the Colombian Amazon. Differences of soil resources were defined by the type and physical and chemical properties of soil: a forest on clay loam soil (Endostagnic Plinthosol) at the Amacayacu National Natural Park and, the other on white sand (Ortseinc Podzol) at the Zafire Biological Station, located in the Forest Reservation of the Calder´on River. We found that the standing crop fine root mass and the production was significantly different between soil depths (0–10 and 10–20 cm) and also between forests. The loamy sand forest allocated more carbon to fine roots than the clay loam forest with the production in loamy sand forest twice (mean±standard error=2.98±0.36 and 3.33±0.69MgC ha−1 yr−1, method 1 and 2, respectively) as much as for the more fertile loamy soil forest (1.51±0.14, method 1, and from 1.03±0.31 to 1.36±0.23MgC ha−1 yr−1, method 2). Similarly, the average of standing crop fine root mass was higher in the white-sands forest (10.94±0.33MgC ha−1) as compared to the forest on the more fertile soil (from 3.04±0.15 to 3.64±0.18MgC ha−1). The standing crop fine root mass also showed a temporal pattern related to rainfall, with the production of fine roots decreasing substantially in the dry period of the year 2005. These results suggest that soil resources may play an important role in patterns of carbon allocation to the production of fine roots in these forests as the proportion of carbon allocated to above- and below-ground organs is different between forest types. Thus, a trade-off between above- and below-ground growth seems to exist with our results also suggesting that there are no differences in total net primary productivity between these two forests, but with higher below-ground production and lower aboveground production for the forest on the nutrient poor soil.